ANALISIS FRAMING PEMBERITAAN PEMBUNUHAN WANITA HAMIL DI GUNUNGKIDUL PADA MEDIA ONLINE REPUBLIKA.CO.ID DAN KOMPAS.COM - Natasya Putri Hiranti; Hendra Setiawan (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
This article discusses the framing analysis of reporting on pregnant women being killed in Gunungkidul in November 2022. The murder occurred because the victim RN (25) refused to abort her pregnancy as a result of her actions with ER (24). This study uses the Zhongdang Pan and Gerald M Koscki Framing Analysis model. This analysis model assumes that, every news has a frame that functions as the center of idea organization. The media studied are Republika.co.id and Kompas.com, both of which have views on how to package news. The data collection technique is the technique of observing and noting. The research data are textnews Republika.co.idq danq Kompas.com. The results of the research show that in packaging the news, these two media use simple words that are easily understood by the public. The two media have different points of view. Republika.co.id reports the chronology of the arrest of the two perpetrators of the murder by the police, while Kompas.com reports a number of heartbreaking facts in the case of the sadistic murder of RN.